Association of enterolactone with blood pressure and hypertension risk in NHANES. - Cynthia M Weiner; Shannon E Khan; Caleb Leong; Sushant M Ranadive; Sara C Campbell; Jeffrey T Howard; Kevin S Heffernan (PLoS ONE)
The gut microbiome may affect overall cardiometabolic health. Enterolactone is an enterolignan reflective of dietary lignan intake and gut microbiota composition and diversity that can be measured in the urine. The purpose of this study was to examine the association between urinary enterolactone concentration as a reflection of gut health and blood pressure/risk of hypertension in a large representative sample from the US population. This analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES) collected from January 1999 through December 2010. Variables of interest included participant characteristics (including demographic, anthropometric and social/environmental factors), resting blood pressure and hypertension history, and urinary enterolactone concentration. 10,637 participants (45 years (SE = 0.3), 51.7% (SE = 0.6%) were female) were included in analyses. In multivariable models adjusted for demographic, socioeconomic and behavioral/environmental covariates, each one-unit change in log-transformed increase in enterolactone was associated with a 0.738 point (95% CI: -0.946, -0.529; p<0.001) decrease in systolic blood pressure and a 0.407 point (95% CI: -0.575, -0.239; p<0.001) decrease in diastolic blood pressure. Moreover, in fully adjusted models, each one-unit change in log-transformed enterolactone was associated with 8.2% lower odds of hypertension (OR = 0.918; 95% CI: 0.892, 0.944; p<0.001). Urinary enterolactone, an indicator of gut microbiome health, is inversely associated with blood pressure and hypertension risk in a nationally representative sample of U.S. adults.